The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/srep05958
|View full text |Cite
|
Sign up to set email alerts
|

A nucleolytic lupus autoantibody is toxic to BRCA2-deficient cancer cells

Abstract: Cancer cells with defects in DNA repair are highly susceptible to DNA-damaging agents, but delivery of therapeutic agents into cell nuclei can be challenging. A subset of lupus autoantibodies is associated with nucleolytic activity, and some of these antibodies are capable of nuclear penetration. We hypothesized that such antibodies might have potential as therapeutic agents targeted towards DNA repair-deficient malignancies. We identified the lupus autoantibody 5C6 as a cell-penetrating nucleolytic antibody a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Mutations which enhanced the ability of 3E10 scFv fragments to penetrate cell nuclei and precipitate DNA damage have been identified and 3E10 appeared to be particularly toxic to cancer cells with dysregulated DNA repair pathways, for instance with BRCA2 mutations [45,46]. Cellular uptake into tumour cells of 3E10 scFv was enhanced by the presence of extracellular DNA [39], although 3E10 also selectively immunoprecipitated heavy chain of myosin IIb on the cell surface of muscle cells, implying both a role for this protein in cell uptake but also a degree of cross-or poly-reactivity for the antibody [47].…”
Section: Characteristics Of Intracellular and Cell Penetrating Antibomentioning
confidence: 99%
“…Mutations which enhanced the ability of 3E10 scFv fragments to penetrate cell nuclei and precipitate DNA damage have been identified and 3E10 appeared to be particularly toxic to cancer cells with dysregulated DNA repair pathways, for instance with BRCA2 mutations [45,46]. Cellular uptake into tumour cells of 3E10 scFv was enhanced by the presence of extracellular DNA [39], although 3E10 also selectively immunoprecipitated heavy chain of myosin IIb on the cell surface of muscle cells, implying both a role for this protein in cell uptake but also a degree of cross-or poly-reactivity for the antibody [47].…”
Section: Characteristics Of Intracellular and Cell Penetrating Antibomentioning
confidence: 99%
“…Although endosomal trapping has been a major challenge for intracellular functional delivery of RNA, peptides, and antibodies, our confocal microscopic studies with the PS DNA oligo-modified tubulin antibodies show that the delivered antibodies coincide with the tubulin structure. The majority of the current antibody intracellular delivery methodologies are unidirectional (11)(12)(13)(14)(15)(16)(17)(18)(19). This study shows that cellular retention of our modified antibodies requires the presence of a target antigen because the modified nontargeting antibodies, within a relatively short time, become absent in cultured living cells and in treated tumors.…”
Section: Discussionmentioning
confidence: 79%
“…Over the years, multiple studies, primarily in cultured cells, have shown the feasibility of facilitating antibodies' cellular internalization (11)(12)(13). Furthermore, a number of studies have shown the potential of therapeutic benefits in vivo of a nuclear-penetrating lupus anti-DNA autoantibody (14)(15)(16)(17). The anti-DNA autoantibody entered the cell nucleus and was shown to inhibit DNA repair and selectively kill certain cancer cells that are highly vulnerable to DNA damage (16).…”
Section: Introductionmentioning
confidence: 99%
“…Although the intrabody approach relies on straightforward intracellular expression within the same antigen-expressing cells, another strategy is based on the use of the intrinsic ability of several naturally occurring autoantibodies (see Section “Internalization of Antibodies Into Cells Via Normal and Pathological Processes”) to enter the cells. The most straightforward pathway utilizes the recently discovered potential of a subset of cell and nuclear penetrating lupus erythematosus anti-DNA autoantibodies to serve as therapeutic agents targeted toward DNA repair-deficient malignancies ( Hansen et al, 2012 ; Noble et al, 2014 , 2015 ). Specifically, the lupus erythematosus anti-DNA autoantibodies 3E10 ( Hansen et al, 2012 ) and their more potent divalent mutants ( Noble et al, 2015 ), including humanized and re-engineered ones ( Rattray et al, 2018 ), as well as the nucleolytic autoantibody 5C6 ( Noble et al, 2014 ) were shown to bind DNA and either inhibit key steps in DNA repair or damage single-stranded DNA in a manner, making them selectively lethal to cancer cells with defective homology-directed repair of DNA double-strand breaks.…”
Section: Strategies For Intracellular Targeting Of Antibodies Their mentioning
confidence: 99%